Description de la mise en œuvre d'une démarche inductive pour caractériser les perceptions de présence des pairs-apprenants dans le cadre de la réalisation d'activités collectives à distance - Sonia Proust-Androwkha (Centre National d'Enseignement à Distance, 2022)
This article describes an empirical research project using an inductive approach which aimed to understand the way learners, involved in an online training system, perceive the presence of their peers when they interact with them in the context of collective activities in a small group. This research is based on two empirical components; thirty learners, from two cohorts involved in the same online learning system, have contributed to the research. The data set is composed of thirty-six individual interviews carried out between 2018 and 2020 and eighteen phenomenological narratives. Firstly, two quantitative analysis done by statistic treatment of qualitative data give a synoptic view of the vocabulary used in the learners' language. The results of the analysis show the importance that these learners attach to the socio-affective dimension of the interactions between peers. In a second step, three qualitative analysis, performed by analysing with the help of conceptualizing categories (Paillé et Mucchielli, 2016), enable to get deeper into the understanding of the socio-affective dimension of the interactions between peers and, in fine, to contribute to a conceptualisation of the socio-affective presence in on-line learning.